Pengaruh Model Discovery Learning Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 125 Palembang - Desta Ariasanti; M. Taheri Akhbar; Sylvia Lara Syaflin (Universitas Negeri Padang, 2021)
This study aims to determine whether there is an effect to the discovery learning model on science learning outcomes for fourth-grade students of SD Negeri 125 Palembang. This study uses a quasi-experimental research method (quasi-experimental). The design in this study was a nonrandomized control group pretest-posttest design. The population is all fourth-grade students of SD Negeri 125 Palembang. Sampling technique using simple random sampling technique obtained two classes as samples, namely class IV. A as the experimental class and IV. C as control class. The instrument used in the science learning outcomes test for energy source materials is in the form of multiple choice. Testing the data hypothesis in this study using the independent sample t-test. Based on the results of the t-test with tcount = 2,85 while the ttable = 2,011, so the proposed hypothesis can be accepted, namely that there is an influence of discovery learning model on science learning outcomes for fourth grade students of SD Negeri 125 Palembang.